A Radial Line Slot Array (RLSA) Antenna with the Specifications of 16 dBi Outdoor patch Antenna - Teddy Purnamirza; Safrizal Hasbi; Imran M. Bin Ibrahim; Mulyono Mulyono; Fitri Amillia; Depriwana Rahmi (Universitas Ahmad Dahlan, 2018)
It is recommended by several researches that RLSA antennas have possibility as an option for Wi-Fi devices antennas. Therefore, to dig deeper this possibility, we designed a RLSA antenna that mimics the specification of an antenna usually found in market, that is 16 dBi outdoor patch antenna. We carried out a parameterization to get a best RLSA antenna model. The model was then fabricated and measured. The measurement results are quite agrees with the simulation results. We found that with the same size of 0.05 m2, our RLSA antennas has better performance in term of gain (2 dB higher), S11 (7 dB lower), and beamwidth (900 wider) compared to the patch antenna. A significant result is that RLSA antenna has much wider bandwidth (815 MHz wider) compared to the patch antenna. A test to our RLSA antenna as an antenna for Wi-Fi devices shows that it works properly.